Internatıonally Well-Intentıoned but Instıtutıonally Failed: Human Securıty Network - Bülent Sarper Ağir; Orçun Mutlu; Barış Gürsoy (The Review of International Affairs)
The end of the Cold War provided a favourable environment for normative thoughts in the security realm and thus led to the broadening and deepening of security conception. Thereby, some states in global politics have been relatively stripped of traditional security conceptions and can focus on “human security”, which is part of a wide range of security agendas. In this respect, a coalition of states, based on common ground and expectations on human security issues, launched the Human Security Network initiative with the effect of the normative milieu and achievements of the 1990s. However, it faced a myriad of challenges in the 21st century when traditional security conception was re-emphasised, especially in the aftermath of the 9/11 terrorist attacks and subsequent turning point developments such as the 2008 global financial crisis, the Brexit process of the European Union, the failure of the Arab Spring, refugee flows, insufficient global solidarity during the COVID-19 pandemic, and rising authoritarianism in global politics. The purpose of this study is to examine the extent to which the Human Security Network has met its objectives since its founding in light of the difficulties that have contributed to the decline of the global liberal order and its principles, as well as any organisational shortcomings.